Effect from Doping of Quantum Wells on Enhancement of The Mobility Limited by One-Interface Roughness Scattering - Hai, Tran Thi; Tung, Nguyen Huyen; Hong, Nguyen Trung (Communications in Physics, 2011)
We present a theoretical study of the effect from doping of quantum wells (QWs) on enhancement of the mobility limited by one-interface roughness scattering. Within the variational approach, we introduce the enhancement factor defined by the ratio of the overall mobility in symmetric two-side doped square QWs to that in the asymmetric one-side counterpart under the same doping and interface profiles. The enhancement is fixed by the sample parameters such as well width, sheet carrier density, and correlation length. So, we propose two-side doping as an efficient way to upgrade the quality of QWs. The two-interface roughness scattering is also incorporated to make comparison.